Pendampingan Pemasaran Melalui Marketing Mix 4p Pada Produk UMKM dalam Menarik Minat Konsumen - Irmayanti Irmayanti; Yunisari, Ulfa; Suriyati, Suriyati (Jurnal Pelayanan dan Pengabdian Masyarakat Indonesia, 2023)
Marketing strategy is an effort made by a businessman in introducing his product to achieve the desired goals by developing competitive advantages and efforts used to generate profits. The marketing strategy is very important for Micro, Small and Medium Enterprises (MSMEs) in marketing their products. Where in marketing management there are four marketing strategies through the Marketing Mix, namely product, price, place and promotion. The purpose of implementing a marketing strategy through Marketing Mix is ​​to increase product sales and provide an understanding of marketing strategies in order to solve specific problems in marketing. This community service activity was carried out in the Bojo Environment, Awang Tangka Village, Kajuara District, Bone Regency. The results achieved in this activity were an increase in image and sales as well as an increase in knowledge and insight regarding marketing strategies at Mrs. Asriani's MSMEs Pastry Business. The method used in this activity is the socialization method of implementing marketing strategies by utilizing brochures as learning materials.